Endangered Medicinal Plant Taxus baccata Hook. F. and Natural Regeneration status in Himachal Pradesh, India - Singh, Manjeet; Lankar, U.; Zaffar, S. N. (Indian Forester, 2018)
In present study, natural regeneration status of Taxus baccata along with other associated tree species was assessed in three forest divisions of Himachal Pradesh, North Western Himalaya, India. Two sites were selected in each division and were further divided into lower (2500-2700m) and upper (2700-2900m) elevations. The results revealed that the recruitments of Taxus baccata are good enough at higher elevations as compared to lower elevations, but there is no any established regeneration in all three forest divisions. The incidence of over-harvesting and other anthropogenic pressures was comparatively higher at lower elevations, leading to poor regeneration of the species. Associated species showed better recruitments and established regeneration as compared to that of Taxus baccata, which attributed that natural regeneration of this species is being fatally hampered due to exclusive over exploitation. The study suggests that there is an immediate need to protect Taxus bearing forests from harvesting (lopping, peeling bark, etc.), grazing and other destructive activities. The species regenerates poorly from seed. By means of efficient biotechnological tools, artificial regeneration of the species should be promoted in nursery to develop mass scale healthy planting materials. Besides in-situ conservation and management, mass scale afforestation of the species with the participation of local communities in protected forest areas particularly at religious forests need to be done.